LOAD DISTRIBUTION TO REDUCE POWER LOSS IN DISTRIBUTION TRANSFORMERS AT PT PLN (PERSERO) ULP LEMBAYUNG - Novi Kristiani Sidabalok; Hamdani; Adisastra Pengalaman Tarigan (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Load balancing on distribution transformers is an important step to improve the efficiency of electricity distribution and reduce power losses. Load imbalance between phases can cause an increase in neutral current, contributing to conductor power loss and financial loss. This research was conducted on the BR 114 distribution transformer at PT PLN (Persero) ULP Lembayung, with the aim of analyzing the impact of load balancing on neutral current, conductor power loss, and financial loss. The calculation results show that load balancing can reduce the neutral current from 150 A to 97 A, thereby decreasing the neutral conductor power loss from 2.00797 kW to 0.37129 kW. Financially, the savings obtained from load balancing amount to Rp 80,460,399. Thus, load balancing has proven to be an effective solution in reducing power losses and improving the efficiency of electricity distribution.